Supply Chain Management and Automatic Identification Management Convergence: Experiences in the Pharmaceutical Scenario - Barchetti, U.; Bucciero, A.; Guido, A. L.; Mainetti, L.; Patrono, L. (IntechOpen, 2011)
None